2014
DOI: 10.1136/gutjnl-2013-305168
|View full text |Cite
|
Sign up to set email alerts
|

ClC-3 chloride channel/antiporter defect contributes to inflammatory bowel disease in humans and mice

Abstract: A defect in ClC-3 may contribute to the pathogenesis of IBD by promoting intestinal epithelial cell apoptosis and Paneth cell loss, suggesting that modulation of ClC-3 expression might be a new strategy for the treatment of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…These results provide the first and compelling evidence that ClC-3 is critically linked to preadipocyte apoptosis induced by saturated FFA in vitro and in T2DM. ClC-3 has been suggested to be essential for apoptosis in a variety of cell types, such as vascular smooth muscle cells [19,34], endothelial progenitor cells [21], tumor and carcinoma cells [38,39] and bronchial and intestinal epithelial cells [20,40,41], and thus may play roles in the disease processes of hypertensive vascular remodeling [19], inflammatory responses [20] and tumor cell death [38]. Our presented data demonstrated that ClC-3 protein expression and cellular apoptosis in preadipocytes could be significantly increased in response to saturated FFAs (palmitate), but not unsaturated FFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results provide the first and compelling evidence that ClC-3 is critically linked to preadipocyte apoptosis induced by saturated FFA in vitro and in T2DM. ClC-3 has been suggested to be essential for apoptosis in a variety of cell types, such as vascular smooth muscle cells [19,34], endothelial progenitor cells [21], tumor and carcinoma cells [38,39] and bronchial and intestinal epithelial cells [20,40,41], and thus may play roles in the disease processes of hypertensive vascular remodeling [19], inflammatory responses [20] and tumor cell death [38]. Our presented data demonstrated that ClC-3 protein expression and cellular apoptosis in preadipocytes could be significantly increased in response to saturated FFAs (palmitate), but not unsaturated FFAs.…”
Section: Discussionmentioning
confidence: 99%
“…ClC-3 has been suggested to be responsible for the volume-regulated outwardly rectifying Cl -currents, thus it may be critical for some basic cellular functions, including neutrophil infiltration [14], vascular smooth muscle ROS generation and inflammatory responses [15][16][17], b cell insulin secretion [18] and cellular proliferation and apoptosis [19][20][21][22]. By using ClC-3 knockout mice, our recent study have shown that ClC-3 deficiency can prevent the angiotensin II-induced apoptosis in endothelial progenitor cells [21] but promote DSS-induced apoptosis of intestinal epithelial cells [20], highlighting the importance of disruption of ClC-3 in apoptosis cell damage under diseased conditions. ClC-3 is also abundantly expressed in preadipocytes [23] where its function is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic IEC death has been implicated as a major homeostatic and pathogenic mechanism of IBD,2 3 and RKIP deficiency inhibits DSS/TNBS-induced IEC apoptosis. The FITC-dextran permeability experiment suggests that RKIP deficiency is helpful in maintaining the integrity of colonic epithelial barrier, which leads to the resistance of RKIP-KO mice to experimental colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoprecipitation assay was performed, as previously described. 24 Briefly, the supernatants were incubated with endophilin A2 (Santa Cruz, CA, USA), ClC-3 (Alomone Labs), or GFP antibodies (Santa Cruz) overnight at 4°C, then incubated with Protein A/G beads (Santa Cruz) for 4 h. Beads were washed three times with lysis buffer and the proteins were separated by Western Blotting.…”
Section: Immunoprecipitation and Western Blot Analysismentioning
confidence: 99%